Fatigue analysis on crack problems in engineering structures with stress concentration - James, Joshua Peter (Nanyang Technological University, 2023)
Offshore Pipelines are used to transport crude oil and gas from offshore oil rigs to coastal oil refineries. These pipes are often located at the seabed and can lie in seawater depths ranging from 50 meters to several thousand meters. As such, these pipes are under enormous pressure from the crushing depths, as every 10m travelled below sea level incurs an increase in pressure of approximately 1 bar. Besides this, offshore pipes are often hundreds of kilometers in length, and is pre-welded in sections before being laid on the seabed. Welding often results in hydrogen diffusion and the cracking that results from it. These cracking comes in many forms such as porosity and cracking often propagates as the pipes are subject to the high dynamic forces acting on it. (Prashant Vashishtha, 2022) The objective of this project is to conduct simulation of force and fatigue analysis on crack problems in offshore pipes that are subjected to concentrated stresses resulting from existing conditions, with emphasis placed on the welded joints and supportive forces holding them in place. Computer simulation via ANSYS Finite Element Software. The focus is to study the impact of the location of a deformity on the build-up of stresses as well as the impact of a welded joint with deformities present.